2011
DOI: 10.1039/c1cc14995d
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid based chiral N-amidothioureas. Acetate anion binding induced chirality transfer

Abstract: N-Amidothioureas generated from amine-dimethylated natural L-phenylalanine and its D-enantiomer bearing a chiral carbon that is by 2 atoms or 3 chemical bonds away from the anion binding site establish chiral communication upon acetate anion binding to the thiourea moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The resultant opposite and coupled Cotton effects at 304 nm and 270 nm suggest that the chirality of the phenylthiourea moiety in 2 has been overturned and extended to the anion-thiourea binding block. 7 The mirror-imaged CD spectra of AcO À -L-2 and AcO À -D-2 solutions (Fig. 3) again confirm that the chirality originates from the phenylalanine residue.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…The resultant opposite and coupled Cotton effects at 304 nm and 270 nm suggest that the chirality of the phenylthiourea moiety in 2 has been overturned and extended to the anion-thiourea binding block. 7 The mirror-imaged CD spectra of AcO À -L-2 and AcO À -D-2 solutions (Fig. 3) again confirm that the chirality originates from the phenylalanine residue.…”
mentioning
confidence: 58%
“…S1, ESI †). 7 The thiourea moiety in 2 is thus turned chiral by simply capping 1 with an achiral glycine residue (Scheme 2), which demonstrates the key role that the glycine residue in 2 plays in facilitating the intramolecular chirality transfer, despite its achiral nature and its distance from the thiourea moiety.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 1D discloses that bSiNPs and gSiNPs exhibit a cotton effect similar to that of L-dopa in 240− 296 nm, which indicates that the above nanomaterials inherited the inherent chirality of L-dopa. The new CD signal at 296−350 nm was generated by the π−π* transition of the aromatic sp 2 domain placed in a chiral environment, 29,30 indicating that chiral bSiNPs and gSiNPs have been successfully fabricated. The absolute quantum yields of the obtained bSiNPs and gSiNPs were 0.3 and 1.9%, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5, we also found that in addition to retaining the chiral signal of cysteine, a new set of signal peaks appeared at 250 nm, indicating that L-NGQDs and D-NGQDs are inherited and transferred in their structure through chirality, induce the generation of new chiral centers. 30,31 Detection of tartaric acid by linear sweep voltammetry.-Here we synthesize chiral inorganic nanomaterials and use them to identify tartaric acid by voltammetry. It can be known from the theory that tartaric acid ionizes in water, and its existing state is different under different pH values, while tartaric acid only exists when the pH value is lower than 3 when the pH value is higher than 5, it will exist as tartrate anions.…”
Section: Resultsmentioning
confidence: 99%